On methods of setting the coordinates of the mouse pointer in the case of alternative options for constructing human-computer interaction - P. V. Peresunko (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The aim of the study is to compare and generalize different methods of contactless setting of computer mouse pointer coordinates. Method. To create a contactless human-machine interface, computer vision technologies are used to select a control point on a video camera frame, with the help of which the computer cursor is moved on the user's monitor. General logical methods of scientific research, namely, generalization, are used. An analysis of the considered cursor coordinate control systems is carried out with the allocation of common parts for further generalization and description of formulas for setting the coordinates of the computer mouse cursor. Scientific works with absolute positioning of the computer cursor and works with control of the cursor position shift relative to its coordinates on the previous frame were taken for analysis. Result. As a result of the analysis, strengths and weaknesses of each of the approaches under consideration were indicated. Absolute positioning requires less time to set the cursor to the desired position. It is determined that cursor shift control is not so demanding on the accuracy of calculating the coordinates of the control point. Formulas are given that generalize the methods of moving the computer cursor. Conclusion. The proposed approach to calculating new coordinates of the mouse pointer allows implementing both presented approaches to positioning the computer cursor in the software system, since each of them has advantages depending on the specific situation.